PELATIHAN KONSEP TRI NGA KI HAJAR DEWANTARA BAGI GURU DI SDNU PEMANAHAN - Syafriza, Azizatul Alif; Ferryka, Putri Zudhah (LPPM Universitas Widya Dharma Klaten, 2025)
The purpose of writing this article is to provide training to teachers, especially at SDNU Sleman, regarding the concept of Tri Nga Ki Hajar Dewantara. The concept of